Structural Analysis in the Novel Renaissance by Kinoysan - Nida Firdaus Albanjari; Akmaliyah; Niqyatul Muna; Nurmeila Adawiah Mubarokah (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2024)
This study analyzes the structure in the novel entitled